Junger Westen '91. - Junger Westen '91 (Recklinghausen : Kunsthalle Recklinghausen, 1991)
Adt, Reinhold ; Albrecht, Petra ; Amrhein, Andreas ; Brandmeier, Monika ; Bürkle, Bettina ; Eberhard, Jörg ; Etzold, Eckhard ; Fiedler, Stephan ; Freudenreich, Eberhard ; Geitel, Matthias ; Grasshoff, Birte ; van Haaren, Bettina ; Hinken, Manfred ; Hoefs, Klaus ; Hoffmann, Bogdan ; Hotzel, Hans-Dirk ; Houwer, Bibiena ; Huth, Michael ; Jansen, Jürgen ; etc.
Junger Westen '91, Kunsthalle Recklinghausen, 20. Oktober bis 1. Dezember 1991
boek